Assessment of topsoil removal as an effective method for vegetation restoration in farmed peatlands - Wang, Yimeng; Wang, Yixiao; Wang, Shengzhong; Wang, Ming; Chai, Wenjie (Frontiers in Environmental Science, 2023)
Peatland areas have dramatically declined in the past century because of the demand for agriculture. Therefore, it is urgent to develop suitable techniques to preserve these unique ecosystems. We studied the effects of topsoil removal on vegetation restoration in silt- and sand-amended peatlands in Changbai Mountain, China. We observed that topsoil removal effectively improved soil nutrient levels and water holding capacity in the silt-amended peatland but exhibited no significant effect on sand-amended peatland. Topsoil removal decreased the species richness in both silt- and sand-amended peatlands but did not have any effect on the plant cover and biomass in the sand-amended peatland. The coverage, density, and aboveground biomass of dominant species, namely, Carex schmidtii, significantly increased after topsoil removal in the silt-amended peatland. The target Carex species was absent from the sand-amended peatland. Redundancy analysis identified that soil water content, soil organic carbon, total nitrogen, and total phosphorus explained the most variance in vegetation composition in the silt-amended peatland. Our results demonstrated that topsoil removal is necessary to reduce the weed seeds and promote the recolonization of peatland species, particularly the tussock-forming Carex, in the silt-amended peatland during restoration.